Bond behaviour of grouted spiral and splice connection under direct axial and flexural pullout load [electronic resource] - Seyed Jamal Aldin Hosseini, 1983- , author (2015)
Thesis (Ph.D (Kejuruteraan Awam)) - Universiti Teknologi Malaysia, 2015